IMPLEMENTING FUNCTION FOCUSED CARE IN AL: MEASUREMENT CHALLENGES AND SOLUTIONS. (11th November 2018) - Resnick, B; Bonner, A
Abstract: Residents in Assisted Living (AL) engage in limited amounts of physical activity and decline functionally more rapidly than their peers in nursing homes. Reasons for decline include resident factors (e.g., comorbidities, age) and setting factors (e.g., caregivers, environments and policies), among others. Residents and families expect that direct care workers will complete necessary care tasks and often become distressed if direct care workers just provide encouragement, cueing or minimal assistance needed to assure that residents walk, dress and bathe at their highest level. Once residents are not allowed or encouraged to perform an activity, they lose the ability and motivation to do so. Implementing a function focused care approach is the best way to prevent functional decline and increased time residents spend in sedentary activity. Function focused care is a philosophy of care that teaches direct care workers to evaluate older adults' underlying capability with regard to function and physical activity and optimize their participation in all activities. Careful consideration has to be given to measurement of outcomes related to implementation of Function Focused Care to determine if this approach has been integrated into routine care within the setting. This symposium will address the best ways to evaluate physical activity of residents, Service Plans for evidence of function focused care, and environment and policies within these settings. Accurate measurement of these outcomes will help to assure that we are providing care to residents that will optimize function and physical activity and help them to age in place.